Characterization of grouper iridovirus isolated from grouper (Epinephelus spp.) in Peninsular Malaysia - Hazeri, Maryam (2016)
Iridovirus infection in marine cultured fishes had caused serious mortalities in Southeast Asian countries especially in marine fishes farmed in Taiwan, Singapore, and Thailand due to grouper iridovirus (GIV) and the impact and extent of this disease is unknown hitherto in Malaysia. This is due to lack of knowledge on the host range, geographical distribution and the differences between strains if any. Hence to elucidate this gap, OIE reference polymerase chain reaction assay was utilized to detect the presence of grouper iridovirus in farmed grouper from Peninsular Malaysia. This current study aimed to examine the histopathological changes, using in-house design primers, sequence analysis of major capsid protein (MCP) gene, isolation of iridovirus in BF-2 and SSN-1 cell lines, biophysical and biochemical characterization and SDS-PAGE for characterization and comparing with other reference nucleotide sequences acquired from GenBank, and experimental infectivity study in red hybrid tilapia. A total of 150 hybrid grouper fish and coral trout samples were collected. Of these, GIV was detected in 27 hybrid grouper fish and coral trout samples and they were asymptomatic and or with mild non-specific lesion. Sequence analysis of MCP gene showed that the strain detected in this study was closely related to the reference of GIV and Ranavirus in an emerging disease which has been causing mortalities in grouper culture farms in Peninsular Malaysia. In addition, phylogenetic analysis of MCP gene revealed that the reference GIV and Ranavirus which were obtained from GenBank and all other strains that were detected in this study were included in genotype 1. Clinical samples were collected from diseased grouper juveniles suspected of Iridovirus infection from marine floating cage fish farms. Some of the fish showed darkening of the body, uncoordinated swimming and skin ulcers. Microscopic examinations of the infected tissues showed severe necrosis with large intracytoplasmic inclusions, vacuolated cytoplasm and degenerated nuclei with marginated chromatin in different tissues. The grouper iridovirus (GIV) was isolated in two fish cell lines i.e. BF-2 and SSN-1. The results showed that BF-2 cell line was more susceptible than SSN-1 to GIV with typical cytopathic effect (CPE) manifesting mainly as cells rounding-up, severe vacuolation and, progressive plaques of rounded-up cells within 3-5 days and complete detachment within 7 dpi. Biophysical and biochemical characterization of GIV isolate were determined by heat treatment, UV irradiation and the stability under effect of chemical disinfectants (ether, formalin, iodine) and pH. The GIV isolate showed susceptibility to heat treatment at 56 ̊C, UV irradiation, different pH ranging between 2 to 11, treatment with 2% formalin and iodine. Since all the infected fish appeared healthy, there was a concern over possible transmission of asymptomatic GIV infection in freshwater fish species. To clarify this, an in vivo infection was conducted to investigate the possible susceptibility of red hybrid tilapia using 0.1 ml (108.5 TCID50/0.1 ml ) inoculum originated from BF-2 cell cultures via intraperitoneal injection. The GIV was able to infect tilapia fish within first week of injection, but the infected fish were asymptomatic. In conclusion, GIV pose serious risk to the Malaysian aquaculture industry as this virus can spread without any sign of disease. In summary, the extent of GIV infection in grouper fish farms, which includes information on pathogenicity and geographical distribution in Peninsular Malaysia have been elucidated in this study. This baseline information is essential to mitigate the spread of this disease. Present study also confirmed the infectivity of 0.1 ml (108.5 TCID50/0.1 ml) of BF-2 cell filtrate to red hybrid tilapia by IP injection. Integration of histopathological results such as confirmatory PCR-assays, sequence analysis of MCP, phylogenetic analysis, isolation virus on BF-2 and SSN-1 cell lines, and SDSpage of virus protein are essential in the diagnosis of grouper Iridovirus infection.